2021
DOI: 10.1177/01455613211033125
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Post-vaccine Smell and Taste Disorders: Report of 6 Cases

Abstract: Post-vaccine olfactory and gustatory disorders are very rare and were reported in patients who received influenza vaccines. In this article, we report 6 cases of post-coronavirus disease 2019 (COVID-19) vaccine olfactory and gustatory disorders in patients with negative nasal swabs. Precisely, olfactory and gustatory dysfunctions were reported in 5 and 1 patients, respectively. Sense disorders occurred after the first injection of AstraZeneca (n = 4) or the second injection of Pfizer (n = 2) vaccines. In 4 cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 9 publications
0
27
0
1
Order By: Relevance
“…A major contributory factor that has permitted countries like Singapore to adopt such methods is their high national vaccination rates and low mortality for COVID-19 patients (estimated to be 0.1% especially for the young and healthy population). However, it has been reported that GD is a possible side effect of COVID-19 vaccinations [175]. In Europe, a small handful of COVID-19 naïve patients reported having new-onset olfactory or taste dysfunction following their COVID-19 vaccinations, but their symptoms lasted for less than two weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major contributory factor that has permitted countries like Singapore to adopt such methods is their high national vaccination rates and low mortality for COVID-19 patients (estimated to be 0.1% especially for the young and healthy population). However, it has been reported that GD is a possible side effect of COVID-19 vaccinations [175]. In Europe, a small handful of COVID-19 naïve patients reported having new-onset olfactory or taste dysfunction following their COVID-19 vaccinations, but their symptoms lasted for less than two weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, a small handful of COVID-19 naïve patients reported having new-onset olfactory or taste dysfunction following their COVID-19 vaccinations, but their symptoms lasted for less than two weeks. It is conjectured that post-vaccine inflammation in the olfactory neuroepithelium could contribute to transient olfactory disorder, but there is little established evidence in the current literature [175]. Should GD become a more common or established side effect of vaccinations, whether temporary or permanent, it might confound the use of GD as a potential early screening symptom for COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…They explain such complication either by post-vaccinal inflammatory reaction of the olfactory neuroepithelium, or by immune reaction to asymptomatic presence of the virus in the neuroepithelium after then vaccination (the prevalence of asymptomatic carriers of the virus ranges from 17.9% to 51%). The absence of nasal congestion makes the former hypothesis unlikely, whilst repeated negative nasal swabs question the latter, so further investigations are needed [25]. Farsalinos and al.…”
Section: Galougahi Et Al Present Us a Case Of A Patient With Clear Unilateral Anosmia During Covid-mentioning
confidence: 99%
“…Several pathophysiologic mechanisms were proposed, including obstruction of the olfactory cleft, infection of the sustentacular supporting cells, injury to olfactory sensory cells via a neuropilin-1 (NRP1) receptor, and injury to the olfactory bulb [8,9]. Despite the variety of the reported conditions related to COVID-19 vaccine, up to date, there is only one reported case in the literature on parosmia post-Pfizer-BioNTech vaccine [10]. This paper reports a unique case of parosmia post-COVID-19 vaccine (AstraZeneca) in a medically free patient.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the variety of the reported conditions related to COVID-19 vaccine, up to date, there is only one reported case in the literature on parosmia post-Pfizer-BioNTech vaccine [ 10 ]. This paper reports a unique case of parosmia post-COVID-19 vaccine (AstraZeneca) in a medically free patient.…”
Section: Introductionmentioning
confidence: 99%